العلاقة بين الإرشاد النفسي الإلكتروني ومستوى الذكاء العاطفي لدى عينة من طالبات المرحلة الثانوية بمحافظة جدة - العتيبي، وفاء سلمان (جامعة الملك سعود - الجمعية السعودية للعلوم التربوية والنفسية - جستن, 2023)
هدف البحث إلى التعرف على مستوى الإرشاد النفسي الإلكتروني بأبعاده المختلفة لدى طالبات المرحلة الثانوية بمحافظة جدة والتعرف على مستوى الذكاء العاطفي بأبعاده المختلفة، وكذلك على طبيعة العلاقة الارتباطية بين الدرجات على متغير الإرشاد الإلكتروني بأبعاده المختلفة، ودرجاتهم على متغير الذكاء العاطفي بأبعاده المختلفة، واتبعت الباحثة المنهج الوصفي الارتباطي المقارن، وتكونت عينه البحث من (362) طالبه، قامت الباحثة ببناء استبانة تضمن (36) عبارة، واستبانة الذكاء العاطفي للباحث (الغرايبة، 2011) وهي مقننة على البيئة السعودية، وتتضمن (43) عبارة، وتبين من النتائج وجود فروق ذات دلالة إحصائية عند مستوى (0.01) بين المتوسط الحقيقي والمتوسط الافتراضي لعينة البحث في الإرشاد النفسي الإلكتروني بأبعاده المختلفة لجانب المتوسط الحقيقي، وكذلك وجود فروق ذات دلالة إحصائية عند مستوى (0.01) بين المتوسط الحقيقي والمتوسط الافتراضي لعينة البحث في الذكاء العاطفي بأبعاده المختلفة لجانب المتوسط الحقيقي. The point of the research to identify the level of electronic counseling in its various dimensions Secondary school students in Jeddah, and to identify the level of emotional intelligence in its various dimensions, AWA on the nature of the correlation between degrees on a variable Electronic counseling with its various dimensions, and their degrees on the emotional intelligence variable in dimensions the researcher followed the descriptive, correlative, comparative approach, and sample of the research was formed Of (362) students, the researcher built a questionnaire that included (36) phrases, and a questionnaire The researcher’s emotional intelligence (Al-Ghariba, 2011), which codified on Saudi environment, It includes (43) phrases, it was found from the results that there were statistically significant differences when The level (0.01) between the real different and the hypothetical sample of the research sample in electronic guidance with its different dimensions to the true side of the average, AWA the presence of differences Statistically significant at the level (0.01) between the mean true and the middle default of the research sample in emotional intelligence with its different dimensions for the mean true side.
Keywords: علم النفس التربوي -- الإرشاد الإلكتروني -- الذكاء العاطفي -- طلبة المرحلة الثانوية